Punishment and reward in islamic education: Implementation at ma hidayatus subban - Anzar Aquil; Triana Hermawati; Ahmad Mustafidin; Santi Ratnawati; Kunfuaidah Latifah; Maskur (Yayasan Azhar Amanaa Yogyakarta, 2025)
This research is motivated by a discrepancy between the ideal principles of Islam and field practices, where rewards and punishments are often applied mechanistically, ineducatively, and without considering students' psychological contexts. Using a descriptive qualitative approach and a case study method, data were collected through in-depth interviews, participatory observation, and documentation. The findings show that the implementation of reward and punishment at MA Hidayatus Subban is carried out regularly and relatively systematically. Rewards are given in both material and symbolic-spiritual forms, such as praise, certificates, and prayers, which have proven effective in enhancing motivation and fostering positive student behavior. Punishments, on the other hand, are applied in an educative manner, including advice, reflective assignments, and familial approaches aimed at developing moral awareness. However, the study also found inconsistencies among teachers in applying reward and punishment, leading to perceptions of injustice among students. The study concludes that the effectiveness of reward and punishment in Islamic education is greatly influenced by teachers’ understanding of spiritual values, sensitivity to students’ psychological conditions, and strong institutional support from the school principal and parental involvement. Rewards and punishments should not be treated merely as technical instruments of classroom management but must be grounded in an educational awareness rooted in Islamic values such as justice, compassion, responsibility, and self-awareness. When applied fairly, proportionally, and contextually—in alignment with the goals of Islamic education within the framework of maqashid al-shariah—educational institutions are expected to shape students who are not only behaviorally compliant but also possess strong moral and spiritual consciousness. Proper implementation of these methods impacts not only student discipline but also serves as a fundamental